Readings in urban theory - Fainstein, Susan S.; Campbell, Scott, 1958- (Chicester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
"Updated with a majority of new readings, the Third Edition of Readings in Urban Theory expands its focus to present the most recent developments in urban and regional theories and policies in a globalized world. Around 75% of the readings included are new for the fourth edition Unifies readings by an orientation toward political economy and normative themes of social justice Expands the focus on international planning, including globalization and theories of development Addresses the full range of core urban theory so as to remain the primary text in courses"--Provided by publisher.
"Over the last two decades great strides have been made in urban theory. Drawing on works in geography, planning, design, history, sociology, political science, and cultural studies, the new Third Edition of Readings in Urban Theory presents the most recent developments in the field while also reflecting its highly interdisciplinary nature. These carefully selected readings -- approximately three quarters new for this edition -- address issues that represent the fundamental underpinnings of urban theory. These include the changing urban and regional system, the social impacts of these policies, the effects of publicly sponsored redevelopment programs, cultural meanings of spatial relations, and many others. In addition, this new edition expands its focus of urban planning issues beyond the U.S. and U.K. to reflect a more globalized world. Collectively, these readings from leading scholars offer both a realistic depiction of the new urban and regional environment and innovative approaches to explaining its underlying causes, meanings, and consequences. By presenting an incisive overview and analysis of the most current theories behind urban and regional development, the Third Edition of Readings in Urban Theory goes a long way in helping us make sense of today's world"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cities and towns; Urban economics